دراسة كفاءة زيت جذور الطيون في مكافحة طفيل فاروا نحل العسل (Varroa destructor) مقارنةً مع استخدام حمض الأوكزاليك. - حبيب, فيصل (Latakia University Journal -Biological Sciences Series, 2019)
أُنجز هذا البحث لاختبار كفاءة زيت جذور الطيون في مكافحة طفيل فاروا نحل العسل Varroa destructor, وتمت مقارنة فاعليته مع نتائج المكافحة بحمض الأوكزاليك تركيز 3%Oxalic acid المستخدم ضد هذا الطفيل، تم اختيار مجموعتين من الخلايا لتنفيذ اختبارين متتاليين لكل من المادتين في تطبيق منفصل خلال الفترة الممتدة بين 10/30و 6/ / 11 2011 مع تحقق شرط المكافحة وهو عدم وجود الحضنة داخل الخلايا . تم نشر3 مل زيت جذور الطيون / طائفةً بمحقن طبي على قمة وجوانب إطارات صندوق التربية لخلايا المجموعة الأولى, وقد أعطى متوسط فاعلية تراوحت بين 93.2 % و 94.2 % بشكل متتالٍ لكل من الاختبارين وبمتوسط قدره93.7 % , بينما أعطى حمض الأوكزاليك بتركيز 3 % / طائفة في محلول مائي رشاً على النحل بواسطة بخاخ يدوي على إطارات الحضنة لخلايا المجموعة الثانية متوسط فاعلية تراوحت بين 92.5 % و93.4 % بشكل متتالٍ لكل من الاختبارين وبمتوسط قدره 92.9 %, أظهر التحليل الإحصائي لاختبارtest - Tأنه لاتوجد فروق معنوية بين متوسط فاعلية كل من زيت جذور الطيون وحمض الأوكزاليك المستخدم ( T = 1.42 على مستوى 0.05), وبناءً على هذا تتسم الزيوت العطرية النباتية بفاعلية عالية ضد طفيل الفاروا , وهو مؤشر هام للابتعاد عن استخدام المبيدات وما تتركه من آثار سيئة في البيئة وصحة نحل العسل ومستهلكي منتجاته , كما أن استخدام حمض الأوكزاليك (OA) في مكافحة طفيل فاروا نحل العسل يعد من أهم وسائل المكافحة الآمنة والرخيصة والتي تضمن الحد من تطور مجتمع الفاروا بفاعلية عالية , دون حدوث تأثيرات سلبية على مجتمع نحل العسل. In this study, the efficiency of the was tested to control the varroa parasite. The efficiency of Inula viscose roots oil was compared with the results of the Oxalic acid %3 effects on this varroa parasite two groups of hives. were chosen to make two tests in sequence differently on each of the two substances during the period 30 l 10 and 6l 11 l 2011 taking the control condition into consideration which demands existing no brood inside the hives . 3m.L. of the inula viscose roots oil was spread by medical syringe on both the top and frames of the first group brood box. The average effectiveness ranged between 93,2 % and 94,2 % in sequence for each of both tests with average 93,7 % when the oxalic acid solution by concentration %3 was spraying on the bees by hand spray gave an efficiency average ranged between 92.5 % and 93.4 % respectively for the two tests with average about 92.9 % statistics analysis to (T- test) showed that there are no significant differences between the efficiency average of the inula viscose roots oil and the oxalic acid, (T=1.42 at the level of 0.05 ) , according to that, the natural essential roots viscose inula oils have great efficiency against t the varroa , and this is an important sign to stop the using of the pesticides which have a bad effects on the environment, bees and consumers of its products. the using of the oxalic acid(OA) to control the bees varroa is one of the most important controlling cheap and safe means which can effectively prevent the development of varroa population without harmful effects on the honey bees population.